2017
DOI: 10.1158/0008-5472.can-17-1463
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytes Promote Medulloblastoma Progression through Hedgehog Secretion

Abstract: Astrocytes, the most abundant type of glial cells in the brain, play critical roles in supporting neuronal development and brain function. While astrocytes have been frequently detected in brain tumors, including medulloblastoma (MB), their functions in tumorigenesis are not clear. Here we demonstrate that astrocytes are essential components of the MB tumor microenvironment. Tumor-associated astrocytes (TAA) secreted the ligand sonic hedgehog (Shh), which is required for maintaining MB cell proliferation despi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
86
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(93 citation statements)
references
References 52 publications
7
86
0
Order By: Relevance
“…The astrocyte secretome is diverse and thus, there are likely a combination of factors in the ACM influencing the MB phenotypes. CCL2, SHH, and IL-4 are astrocyte-secreted factors which have been shown to promote MB phenotypes [8,9,42]. Interestingly, CCL2 secretion from astrocytes [9] was induced by chemotherapy and radiation-induced inflammation and necroptosis in astrocytes.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…The astrocyte secretome is diverse and thus, there are likely a combination of factors in the ACM influencing the MB phenotypes. CCL2, SHH, and IL-4 are astrocyte-secreted factors which have been shown to promote MB phenotypes [8,9,42]. Interestingly, CCL2 secretion from astrocytes [9] was induced by chemotherapy and radiation-induced inflammation and necroptosis in astrocytes.…”
Section: Plos Onementioning
confidence: 99%
“…Previously, we have shown that astrocytes influence breast cancer cell invasion and facilitates its metastasis to the brain [6,7]. In primary brain tumors, such as MB, tumor-associated astrocytes have been found to secrete sonic hedgehog (SHH), which directly increased Nestin expression and proliferation of MB cells derived from a genetic mouse model of SHH MB [8]. Metastatic MB tumor-associated astrocytes were also recently identified to secrete chemokine C-C ligand 2 (CCL2), which enriched stem cell properties in MB cells, including expression of CD133 [9].…”
Section: Introductionmentioning
confidence: 99%
“…This effect still required SMO and it was blocked by SMO inhibitors [26]. The source of SHH in vivo was shown to be tumour-associated astrocytes.…”
Section: The Non-canonical Hedgehog Pathwaymentioning
confidence: 99%
“…Experiments performed in triplicate showed consistent results. Compared with control, *P < 0.05 because of high specificity for tumor cells and low toxicity to normal tissue [37][38][39].…”
Section: Discussionmentioning
confidence: 99%